Trends among Flux, Luminosity, and Color Indices in High Redshift QSOs - Kurapati, Datta; Dubagunta, Varun; Mitra, Shyamal (Journal of Student Research, 2023)
The following study discusses the relationship of high redshift(z) Quasi Stellar Objects’(QSOs) flux, luminosity, and color indices. The paper analyzes observable trends among these 3 variables and uses them to understand the distribution of QSOs across space-time. While many such studies have been conducted in redshift ranges of 1<z<4, the following research or study has been done in the relatively unexplored date range of 2 <z<7. To answer this question, we used the Sloan Digital Sky Survey to obtain samples, curate the data, and analyze it using Python Data Science tools including Pandas and Matplotlib. The results suggest a general trend of increasing data density with the progression of distance and convergence of QSO Magnitude distributions about the median. This research provides insight into the evolution of QSOs over space-time and why they occurred.